Development of Surgical Management in Primary Rhegmatogenous Retinal Detachment Treatment from 2009 to 2015. (3rd April 2018) - Eibenberger, Katharina; Georgopoulos, Michael; Rezar-Dreindl, Sandra; Schmidt-Erfurth, Ursula; Sacu, Stefan
ABSTRACT: Purpose : To evaluate the evolution of surgical methods over a 7-year period in patients with primary rhegmatogenous retinal detachment (RRD) and its relation to functional outcome and intra- and postoperative complications. Methods : This prospective observational study included 628 patients with primary RRD who underwent surgical repair between January 2009 and December 2015. The main outcome measures were the type of surgical procedure ((scleral buckle (SB), pars plana vitrectomy (PPV), combination of SB and PPV or cryocoagulation (CC)) and intraocular tamponades. In addition, functional outcome and intra/postoperative complications were assessed over the observational period. Results : During the 7-year observation, the percent of SB procedures decreased from 40.5% in 2009 to 2.7% in 2014, while PPV increased from 38% in 2009 to above 90% in 2014. In 2015, the SB procedure was performed in 10.3% and PPV in 85.6% of patients with RRD ( p < 0.001). No consistent trend was observed for the use of intraocular gas tamponade. The functional outcome within the 7-year observation ranged from 0.25 ± 0.31logmar in 2012 to 0.42 ± 0.40logmar in 2009 and showed no statistically significant trend ( p = 0.28). Intraoperative complications did not change between 2009 and 2015. The rate of cataract surgery and epiretinal membrane development did not change ( p = 0.27; p = 0.09). The percent of re-detachment ranged from 6.2 to 16.5% within the observational period ( p = 0.14). Conclusion : A shift toward PPV alone for primary RRD repair was observed during the 7-year observation. No decrease in functional outcome or increase of intra- and postoperative complications or decrease of primary and final anatomic success rate was observed following the change in surgical procedure.